Price spikes and world food security. The need for change - Daviron, Benoit (Perspective, 2012)
<span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The recent food price increases in international markets threaten food security and have led many researchers, policy makers and NGOs to analyse them in order to address them. Most analysts talk about price spikes, which they characterise in terms of price volatility. This characterisation leads them to advocate measures – market liberalisation, private risk management instruments, and safety nets – that have been showing their limitations for almost 30 years. Clearly there is a certain level of volatility inherent in agricultural product prices, which has been compounded by trade policies and speculation. But since 2005, a steady upward trend in food prices has been observed, sometimes resulting in spikes. Several factors can explain these spikes: the lack of coordinated storage; insufficient and inappropriate agricultural investment; the depletion of resources; and growing demand from biofuels and emerging countries. Placing these spikes within the context of an upward trend opens new avenues for national and global action that depart from the predominant vision today: basing the rules of international trade on food security; coordinating storage policies at the global level; investing in ecological agriculture; and limiting growth in demand for agricultural products."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">Version française de l'article <span style="font-size: 10pt; font-family: Arial; font-style: normal;" data-sheets-value=""1":2,"2":"The recent food price increases in international markets threaten food security and have led many researchers, policy makers and NGOs to analyse them in order to address them. Most analysts talk about price spikes, which they characterise in terms of price volatility. This characterisation leads them to advocate measures – market liberalisation, private risk management instruments, and safety nets – that have been showing their limitations for almost 30 years. Clearly there is a certain level of volatility inherent in agricultural product prices, which has been compounded by trade policies and speculation. But since 2005, a steady upward trend in food prices has been observed, sometimes resulting in spikes. Several factors can explain these spikes: the lack of coordinated storage; insufficient and inappropriate agricultural investment; the depletion of resources; and growing demand from biofuels and emerging countries. Placing these spikes within the context of an upward trend opens new avenues for national and global action that depart from the predominant vision today: basing the rules of international trade on food security; coordinating storage policies at the global level; investing in ecological agriculture; and limiting growth in demand for agricultural products."" data-sheets-userformat=""2":585,"3":[null,0],"6":"1":["1":2,"2":0,"5":[null,2,0],"1":0,"2":0,"3":3,"1":1,"2":0,"4":1],"9":0,"12":0">The recent food price increases in international markets threaten food security and have led many researchers, policy makers and NGOs to analyse them in order to address them. Most analysts talk about price spikes, which they characterise in terms of price volatility. This characterisation leads them to advocate measures – market liberalisation, private risk management instruments, and safety nets – that have been showing their limitations for almost 30 years. Clearly there is a certain level of volatility inherent in agricultural product prices, which has been compounded by trade policies and speculation. But since 2005, a steady upward trend in food prices has been observed, sometimes resulting in spikes. Several factors can explain these spikes: the lack of coordinated storage; insufficient and inappropriate agricultural investment; the depletion of resources; and growing demand from biofuels and emerging countries. Placing these spikes within the context of an upward trend opens new avenues for national and global action that depart from the predominant vision today: basing the rules of international trade on food security; coordinating storage policies at the global level; investing in ecological agriculture; and limiting growth in demand for agricultural products.